Moving towards good agricultural practices (GAPs) through more scientific information - Kant, Lakshmi; Khulbe, Rajesh Kumar; Joshi, Kushagra; Meena, Vijay Singh; Vasudeo, Chaudhari Ganesh; Pattanayak, Arunava (Indian Farming, 2020)
Latest agricultural technologies and information need to be taken to the door steps of all the stakeholders within agriculture domain particularly to the farmers. Proper dissemination of this information to the farmer has been the major bottleneck in boosting crop production with quality, even though numerous technologies are available. The contribution of knowledge as a factor of production is being increasingly given central importance in economic development. Indeed, agriculture has become knowledge intensive, changing rapidly, and making farm management more complex. Skills and knowledge are becoming more critical for success. At such times, the efforts of ICAR-VPKAS, Almora in bridging the information gap among farmers under Mera Gaon Mera Gaurav (MGMG) programme as a ray of hope for future success of agricultural interventions in this area.